A feasibility study of eye gaze with biofeedback in a human-robot interface. Issue 2 (4th March 2022) - Sakamaki, Isao; Adams, Kim; Tavakoli, Mahdi; Wiebe, Sandra
ABSTRACT: Play is a vital activity in which children learn skills and explore the environment through object manipulation. Assistive robots have been used to provide access to play, and Forbidden Region Virtual Fixture (FRVF) guidance at the user interface could help the users make the robot traverse the play environment more efficiently because it behaves like virtual walls to follow. Eye gaze was used to indicate the user's intended target and generate the location of the virtual walls in a card sorting task. We eliminated the typical computer screen required for visual feedback to confirm gaze location, and examined the use of alternative feedback. In this feasibility study, first a group of adults without physical impairment tested the system with auditory and vibrotactile feedback modalities for the gaze fixation and with the virtual walls on and off for robot movement. Then case studies with children and individuals with physical impairments were performed. Even though gaze fixation feedback and the virtual wall did not improve the performance of adult participants without impairment, the feedback increased the speed and accuracy of the gaze fixation and the virtual walls improved the movement efficiency for the participants with impairment and a 6-year-old child without impairment.